Efecto de diferentes fuentes y niveles de azufre en la composición y crecimiento del algodonero - Ramírez Martínez, G.F. (IICA, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),1971